Risk of diabetic retinopathy at first screen in children at 12 and 13 years of age. Issue 12 (19th October 2016) - Scanlon, P. H.; Stratton, I. M.; Bachmann, M. O.; Jones, C.; Leese, G. P.; ,
Abstract: Aims: To investigate the relationships between age at diagnosis of diabetes, age at diabetic eye screening and severity of diabetic retinopathy at first and subsequent screenings in children aged 12 or 13 years. Methods: Data were extracted from four English screening programmes and from the Scottish, Welsh and Northern Irish programmes on all children with diabetes invited for their first and subsequent screening episodes from the age of 12 years. Retinopathy levels at first and subsequent screens, time from diagnosis of diabetes to first screening and age at diagnosis in years were calculated. Results: Data were available for 2125 children with diabetes screened for the first time at age 12 or 13 years. In those diagnosed with diabetes at 2 years of age or less, the proportion with retinopathy in one or both eyes was 20% and 11%, respectively, decreasing to 8% and 2% in those diagnosed between 2 and 12 years ( P < 0.0001). Only three children (aged 8, 10 and 11 years at diagnosis of diabetes) had images graded with referable retinopathy and, of these, two had non‐referable diabetic retinopathy at all subsequent screenings. Of 1703 children with subsequent images, 25 were graded with referable diabetic retinopathy over a mean follow‐up of 3.1 years, an incidence rate of 4.7 (95% confidence interval, 3.1–7.0) per 1000 per year. Conclusions: In this large cohort of children, the low prevalence and incidence rates of referable diabetic retinopathy suggest that screening earlier than age 12 is not necessary. What's new?: This is the largest reported study in the literature of baseline levels of diabetic retinopathy in the age group 12 or 13 years. This is the largest reported study showing the rate of progression of diabetic retinopathy in adolescents. Of 2125 children with diabetes screened for the first time at age 12 or 13 years, three were found to have referable disease. The absence of referable disease in subsequent screens in two of the children and of pre‐proliferative changes in the third child suggest that it is unlikely that any treatment is required.